(untitled) (Open Herald: Periodical of Methodical Research, 2024)
This article primarily discusses the importance of simultaneous translation in linguistic studies. It also provides guidance on how to accurately translate specialized words related to linguistics. The article aims to demonstrate how simultaneous translation can enhance linguistic abilities. Additionally, it explores various approaches to synchronous translation in conferences and meetings, offering effective strategies for successful communication.